(untitled) (Journal of Engineering, 2015)
In this study, a simulation model inside a channel of rectangular section with high of (0.16 m) containing two rectangular obstruction plates were aligned variable heights normal to the direction of flow, use six model of the obstructions height of (0.059, 0.066, 0.073, 0.08 and 0.087 m) were compared with the flow behavior of the same duct without obstructions. To predict the velocity profile, pressure distribution, pressure coefficient and turbulence kinetic energy flow of air, the differential equations which describe the flow were approximated by the finite volumes method for two dimensional, by using commercial software package (FLUENT) with standard of k-ε model two dimensions turbulence flow. The obtained results show that the velocity and the turbulence kinetic energy increase with increasing the obstructions height perpendicular to the flow direction. Streamlines contours used to show mixing of averaged flow-field in one pitch length. The streamlines helped to distinguish between important separated regions of the flow as well. Compared the first model of height of obstruction (0.059 m) with the fifth model of the obstruction of height (0.087 m) it is obtained an increasing in velocity about of (71 %) at the first obstruction and an increasing about (47 %) at the second obstruction. The data obtained by simulation are matching with previous the literature value.